Testicular fusocellular rhabdomyosarcoma as a metastasis of elbow sclerosing rhabdomyosarcoma: A clinicopathologic, immunohistochemical and molecular study of one case - Martorell Miguel; Ortiz Cristian M; Garcia Jose (BMC, 2010)
Abstract Sclerosing rhabdomyosarcoma (SRMS) is an infrequent variant of rhabdomyosarcoma characterized by extensive intercellular hyaline fibrosis. We report the case of a 37 year-old male with a 9 × 6 cm SRMS on the right elbow. Histologically, the tumor showed an abundant extracellular hyaline matrix with extratumoral vascular emboli and microscopic foci of fusocellular embryonal rhabdomyosarcoma (FRMS) separated by a fibrotic band from the sclerosing areas. One year later the patient presented with a right intratesticular tumor of 1.2 × 0.8 cm, which was reported as pure FRMS. Immunohistochemically, SRMS was positive only for MyoD1 and Vimentin and negative for Myogenin and Desmin. Both the elbow emboli with the extratumoral foci of FRMS and the intratesticular tumor were positive for Myogenin, MyoD1, Vimentin and Desmin. Using fluorescent in situ hybridization (FISH), the SRMS and the FRMS tumor cells of the elbow and the FRMS tumor cells of the testis were found to be negative for FOXO1A translocation in chromosome 13. PCR chimeric transcriptional products PAX3-FKHR and PAX7-FKHR were not found. Six months following testicular resection, the patient died of multiple metastases in the mediastinum, lung and right thigh.